Sleep disturbance in dementia or mild cognitive impairment: a realist review of general practice - Aryankhesal, A; Blake, J; Wong, G; Megson, M; Briscoe, S; Allan, L; Broomfield, N; Eastwood, Z; Greene, L; Hilton, A; Killett, A; Lazar, A; et al. (Royal College of General Practitioners, 2023)
Background: Sleep disturbance (SD) is a prevalent condition among people living with dementia (PLwD) or mild cognitive impairment (MCI). Its assessment and management within primary care is complex due to the comorbidities, older age and cognitive impairment typical of this patient group. Aim: This study aimed to explore how primary care clinicians assess, understand, and manage SD for PLwD or MCI; if and why such initiatives work; and how people and their carers experience SD and its treatment. Design and setting: A realist review of existing literature was conducted in 2022. Methods: Six bibliographic databases were searched. Context-Mechanism-Outcome Configurations (CMOCs) were developed and refined. Results: Sixty records were included from 1,869 retrieved hits and 19 CMOCs were developed. Low awareness of and confidence in the treatment of SD among primary care clinicians and service users, combined with time and resource constraints, meant that identifying SD was difficult and not prioritised. Medication was perceived by clinicians and service users as the primary management tool, resulting in inappropriate or long-term prescription. Rigid nursing routines in care homes were reportedly not conducive to good quality sleep. Conclusion: In primary care, SD among PLwD or MCI is not adequately addressed. Over-reliance on medication, under-utilisation of non-pharmacological strategies, and inflexible care home routines were reported due to low confidence and resource constraints. This does not constitute effective and person-centred care. Future work should consider ways to tailor the assessment and management of SD to the needs of individuals and their informal carers without overstretching services.